Bacterial cellulose : from culturing to the development of functional materials - Sundaravadanam Vishnu Vadanan (Nanyang Technological University, 2020)
Cellulose is the most abundant biopolymer found in the biosphere with plant as the major source. It is a representative of microbial exopolysaccharides. Bacterial cellulose (BC) is produced in much lesser extent but it is chemically pure. The absence of hemicellulose and lignin distinguishes it from plant cellulose. BC is a product of primary metabolism and serves as protective envelope. The presence of ultrafine reticulated structure resulted in BC having unique material properties, making it suitable for diverse applications. However, wider applications of this exopolysaccharide is limited due to the inadequate understanding of the bacteria and large scale production of the polymer. The goal of this project is to develop tools to understand the biology of the bacteria and optimization of the culture conditions for enhanced BC production. We also, attempt to understand the assembly of cellulose fibres and the role of cellulose synthase enzyme in the process of cellulose production. With basic understanding of the bacteria and the self-assembly of cellulose nanofibers, it lead to the development of new BC-based functional materials for biomedical applications through sustainable approaches. We designed a surface growth platform to understand the chemotactic behaviour of the bacteria and the impact of cellulose production. The platform is based on surface growth pattern of the organism and it allows us to confirm that cellulose fibrils produced by the bacteria play a pivotal role towards their chemotaxis. The platform efficiently determines the impacts of different growth conditions on cellulose production and is translatable to static culture conditions. The analytical platform provides a means for fundamental biological studies of bacteria chemotaxis as well as systematic approach towards rational design and development of scalable bioprocessing strategies for industrial production of bacterial cellulose. Upon identification of the highest cellulose producing bacteria, the process of formation and assembly of cellulose chains was investigated. The substrate specificity of cellulase synthase enzyme was explored for the process of exopolysaccharide production. With preliminary idea regarding the process of polymerization and crystallization, new tunable functional materials can be designed to control the biodegradability of BC based composites. There is also, a clear indication that the substituted glucose substrates were not modified post polymerization and assembly of cellulose chains. BC was combined with different classes of materials, conductive polymers, and amyloid fusion proteins through sustainable methods. A top-down strategy was employed to design BC-PEDOT:PSS conductive aerogels with high conductivity values (0.7 Scm-1), as substrates for flexible electronics. Bioinspired bottom-up strategy employed to design BC-based magnetic membranes, functionalized with magnetite nucleating peptide domains (m6A peptide), for improved wound healing applications. Through this strategy, high saturation magnetization of 40 emug-1 was obtained for BC-m6A membranes, four times higher than normal ex situ BC doping. The BC-m6A membrane displayed exceptional wound healing capabilities in the presence of the magnetic field and improved wound healing by 61%. Our simple design strategy and optimization adopted for obtaining a hybrid functional material for use in the development of biomedical devices, is unquestionably low-cost, facile, and highly efficient approach. The hybrid functional materials developed display potential in biomedical applications.